Republic of Madagascar : Technical Assistance Report-Government Finance Statistics. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2022)
At the request of the Ministry of the Economy and Finance (Ministere de l'Economie et des Finances (MEF)) and in consultation with the African Department (AFR) of the International Monetary Fund (IMF), the IMF Statistics Department (STA) carried out a remote mission on government finance statistics (GFS) from November 29-December 10, 2021. The purpose of the mission was to continue to support the Malagasy authorities in their work to adopt international standards of the Government Finance Statistics Manual 2014 (GFSM 2014) for their GFS. The mission would like to thank the Research Directorate (Direction des Etudes (DE)) of the Directorate General of the Treasury (Direction Generale du Tresor (DGT)) for its close collaboration and more specifically for the timely communication of the required documents, which was essential to the success of the mission given the remote working conditions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Madagascar, Republic of